PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA PEMROGRAMAN DASAR C++ MENGGUNAKAN ADOBE FLASH CS6 PADA SISWA KELAS X SMK AL-ITTIHAD JUNGPASIR WEDUNG DEMAK - Najib, Muhammad Najib (Joined Journal (Journal of Informatics Education), 2019)
ABSTRACT The development of this learning media uses the Research and Development (R & D) method which consists of ten process stages: potential and problems, data collection, product design, design validation, product design revision, product testing, product revision, usage testing, revision product, mass production. Testing is done using alpha testing and beta testing. Alpha testing by knowing the performance and validation by expert judgment, namely media experts and material experts. Beta testing is tested on students. Beta testing is done after alpha testing gets a very valid validation result. Beta testing uses a Likert scale to students containing student responses to the use of learning media. Data retrieval was carried out at AL-ITTIHAD Vocational School in Wedung Demak Jungpasir involving 32 students for instrument testing. The data obtained were then analyzed by descriptive and quantitative analysis techniques by changing the data of the average assessment results into the interval of the feasibility score. The results obtained from media expert validators were 73% in the feasible category, material experts at 98% in the very feasible category. While the results of student responses to media in the field scored 92% with a very decent category. So that it can be concluded as a whole that the learning media of the basic programming language C ++ uses Adobe Flash CS6 for class X AL-ITTIHAD VOCATIONAL SCHOOL, Wedung Demak Jungpasir is very feasible to use.  Keywords: Development of learning media, Basic C ++ Programming Language, Adobe Flash CS6.